Difficulties and/or facilities experienced by the Family Health Strategy professionals - Pinto, Érika Simone Galvão; Menezes, Rejane Maria Paiva (Online Brazilian Journal of Nursing, 2008)
PROBLEM: Does the professional formation influence the Family Health Strategy (FHS) professionals’ experiences? OBJECTIVE: to analyze the facilities and difficulties experienced by the professionals of the FHS. METHODOLOGY: Descriptive and quantitative study realized at Ceará-Mirim, Rio Grande do Norte state, Brazil. A questionnaire was applied to 190 FHS professionals. The results were analyzed by frequencies, means and standard deviation. RESULTS: There is a predominance of the female gender (n=137) and the mean age is 38.9 (sd=7.8). The most developed activities are health care actions for doctors and nurses, oral hygiene for dentists, immunization for the nurses’ aides, educative meetings for the dental auxiliaries (ACD), and home visit for the Community Health Agent (ACS). About the work facilities, 93.2% reported to be the presence of professionals with public health profile. Concerning the difficulties, 86.8% of the professionals mentioned the unavailability of materials, followed by the salary range (81.6%). The drug unavailability is considered as difficulty degree one by ACS and doctors; the kind of contractual bond was mentioned as degree two by ACD and dentists; and in degree three the salary range was mentioned by dentists and nurses’ aides. CONCLUSION: the difficulties faced by the FHS professionals are divergent among them.